Analisis Pengaruh Rasio Profitabilitas terhadap Pertumbuhan Laba pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) (Studi Kasus PT. BTPN Syariah Tbk di Tahun 2017-2021) - Dio Ahmad Fawzi (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2022)
The purpose of this study is to understand the Analysis of the Effect of Profitability Ratio on Profit Growth in Banking Companies Listed on the Indonesia Stock Exchange (IDX) (Case Study of Pt. Btpn Syariah Tbk in 2017-2021). The profitability ratio is a ratio to assess the company's ability to seek profit. This ratio also provides a measure of the level of management effectiveness of an enterprise. Profit growth is a ratio that shows the company's ability to increase net profit compared to last year. This research according to its data analysis includes an associative quantitative approach. Associative quantitative research is research that aims to determine the influence or relationship between two or more variables using data in the form of numbers. The results showed a regression calculation that Return on Assets (ROA) had a significant effect on PT. BTPN Syariah Tbk. This is evidenced by the significance value (Sig) (0.00) smaller than (α) 0.05. Regression calculation that Return on Equity (ROE) does not have a significant impact on PT. BTPN Syariah Tbk. This is evidenced by the significance value (Sig) (0.171) greater than (α) 0.05. And regression calculations show that Return on Assets (ROA) and Return on Equity (ROE) together (simultaneously) have a significant effect on PT. BTPN Syariah Tbk. is evidenced by the value (Sig) of 0.00 less than (α) 0.05. So it can be concluded that there is a positive and significant influence of the variables Return on Assets (ROA) and Return on Equity (ROE), simultaneously or simultaneously on the profit growth of PT. BTPN Syariah Tbk.